Assessment of Forestry Extension Service Delivery among Rural Farmers Living around Awi Forest Reserve in Cross River State, Nigeria - E. D. Udoh; B. I. Ogar; I. E. Ema; E. O. Samson (Journal of Applied Sciences and Environmental Management)
This study assessed forestry extension service delivery among rural farmers living around the Awi Forest Reserve in Cross River State, Nigeria. A total of 214 respondents were selected using a multistage sampling technique. Data were collected through structured questionnaires and analyzed using descriptive statistics and a 5-point Likert scale. The results showed that the average age of respondents was 39 years, with 61% being male and 85% married. Most respondents (53%) had primary education, and 57% operated on small farm sizes of 1-2 hectares. Farmers expressed satisfaction with campaigns against forest fires (mean = 3.58), forest management practices (mean = 3.35), and information on forestry laws (mean = 3.34). However, dissatisfaction was recorded for training on agroforestry (mean = 2.77), seedling distribution (mean = 1.75), and budding and grafting (mean = 1.54). Major constraints to effective service delivery included inadequate extension agents (mean = 4.0), poor supervision (mean = 3.53), and insufficient funding (mean = 3.48). The findings highlight the urgent need to address these challenges to enhance sustainable forest management and conservation efforts in the study area.